Occupation and maternal mortality in Brazil - Feitosa-Assis, Ana Isabela (Rev Saude Publica, 2020)
OBJECTIVE: To estimate maternal mortality ratio according to occupation in Brazil. METHODS: This is a mortality study conducted with national data from the Mortality Information System (SIM) and the Live Birth Information System (SINASC) in 2015. Maternal mortality ratios were estimated according to the occupation recorded in death certificates, using the Brazilian Classification of Occupation (CBO), version 2002. RESULTS: A total of 1,738 maternal deaths records were found, corresponding to a maternal mortality ratio of 57.6/100,000 live births. It varied among occupational groups, with higher estimates among service and agricultural workers, particularly for domestic workers (123.2/100,000 live births), followed by general agricultural workers (88.3/100,000 live births). Manicurists and nursing technicians also presented high maternal mortality ratio. Maternal occupation was not reported in 17.0% of SIM registers and in 13.2% of SINASC data. Inconsistent records of occupation were found.“Housewife” prevailed in SIM (35.5%) and SINASC (39.1%). CONCLUSIONS: Maternal mortality ratio differs by occupation, suggesting a work contribution, which requires further research focusing occupational risk factors. Socioeconomic factors are closely related to occupation, and their combination with work exposures and the poor access to health services need to be also addressed.